Penerapan Model Discovery Learning Terhadap Kemampuan Pemahaman Konsep Matematis Siswa Kelas XI SMA PGRI 2 Padang - Safitri, Mutia; Rahmi; Aima, Zulfitri (Prodi Pendidikan Matematika Universitas PGRI Ronggolawe, 2024)
This study aims to find out whether students' understanding of mathematical concepts after applying the discovery learning model is better than before applying the discovery learning model. This type of research is Pre Experimental Design research with its design form: One-Group Pre-test & Post-test. The study population is Class XI students of SMA PGRI 2 Padang for the 2023/2024 academic year consisting of 2 classes. The sampling technique is carried out (Purposive Sampling). The instruments used in this study were pre-test and post-test in the form of essays. The test statistics used for hypothesis testing are the Paired Sample T-Test. The results of the hypothesis test were obtained = 13.711 and = 2.060. Because is greater than , the is rejected with a real rate of 0.05 and means that the hypothesis is accepted. So it can be concluded that students' understanding of mathematical concepts by applying the discovery learning model is better than before applying the discovery learning model